Influence mechanisms of textile-dyeing sludge characteristics on degradation of anilines by integrated ultrasound-permanganate treatment. (10th May 2017) - Liang, Jieying; Ning, Xun-an; Lai, Xiaojun; Zou, Haiyuan; Sun, Jian; Lu, Xingwen; Zhang, Yaping; An, Taicheng
Abstract: In order to support the use of integrated ultrasound-Mn(VII) for the removal of anilines, this study investigated for the first time the influence of the sludge characteristics on the reaction kinetics of target anilines including o-toluidine, p-chloroaniline, 2-methoxy-5-methylaniline, and 2, 4, 5-trimethylaniline. The results indicated that with a KMnO4 dosage of 1 mM and an ultrasound power density of 0.90 W cm −3, 68.85%, 85.53%, and 78.50% of anilines can be removed from textile sludge plant 1, 2, and 3. Higher removal efficiency of anilines was achieved at a lower pH value, smaller particle size, and more negative ζ-potential. The target anilines exhibited substantial reactivity toward Mn(VII) with the maxima of second-order rate constants at a pH value near their pKa values for o-toluidine (0.80 M −1 s −1  at pH 4), p-chloroaniline (0.65 M −1 s −1  at pH 4), 2-methoxy-5-methylaniline (0.45 M −1 s −1  at pH 4), and 2, 4, 5-trimethylaniline (0.34 M −1 s −1  at pH 5). Moreover, the biodegradability of textile-dyeing sludge was greatly enhanced by integrated ultrasound-Mn(VII) treatment. This integrated treatment was proposed as an effective method for the disposal of anilines in textile-dyeing sludge. Highlights: US-Mn(VII) was effective in degradation of anilines in three textile-dyeing sludges. The anilines removal was affected by organic matter, pH, particle size, ζ-potential. Anilines show marked reactivity toward Mn(VII) with the maxima of kMn(VII) at pH ≈ pKa . The biodegradabilities of sludges can be greatly enhanced by US-Mn(VII) treatment.